Synovial volume vs synovial measurements from dynamic contrast enhanced MRI as measures of response in osteoarthritis. Issue 8 (August 2016) - Gait, A.D.; Hodgson, R.; Parkes, M.J.; Hutchinson, C.E.; O'Neill, T.W.; Maricar, N.; Marjanovic, E.J.; Cootes, T.F.; Felson, D.T.
Summary: Objective: Synovium is increasingly a target of osteoarthritis (OA) treatment, yet its optimal measurement is unclear. Using dynamic contrast enhanced (DCE) MRI in knee OA patients before and after intraarticular steroid injection, we compared the responsiveness of static synovial volume measures to measures of dynamic changes in synovial enhancement, changes that are strongly related to synovial vascularity. Methods: Ninety three patients underwent DCE-MRI before and 1–2 weeks after intra-articular injection of 80 mg methylprednisolone. Synovium was segmented and volume, relative enhancement rate (RER), maximum relative enhancement (REmax ), late relative enhancement (RElate ) and pharmacokinetic parameters (K trans, ve ) were calculated. KOOS (​knee injury and osteoarthritis outcome score) pain score was recorded before and after injection. Standardized change scores were calculated for each parameter. Linear regression and Pearson's correlations were used to investigate the relationship between change in MRI parameters and change in pain. Results: The change in standardized score for the measures of synovial enhancement, RElate and REmax were −0.58 (95% CI −0.79 to −0.37) and −0.62 (95% CI −0.83 to −0.41) respectively, whereas the score for synovial volume was −0.30 (−0.52 to −0.09). Further, change in knee pain correlated more strongly with changes in enhancement (for both REmax and RElate, r = −0.27 (95% CI −0.45 to −0.07)) than with changes in synovial volume −0.15 (−0.35 to 0.05). Conclusion: This study suggests DCE-MRI derived measures of synovial enhancement may be more sensitive to the response to treatment and more strongly associated with changes in pain than synovial volume and may be better outcomes for assessment of structural effects of treatment in OA.